2020
DOI: 10.1038/s41467-020-17699-z
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian histones facilitate antimicrobial synergy by disrupting the bacterial proton gradient and chromosome organization

Abstract: First proposed as antimicrobial agents, histones were later recognized for their role in condensing chromosomes. Histone antimicrobial activity has been reported in innate immune responses. However, how histones kill bacteria has remained elusive. The co-localization of histones with antimicrobial peptides (AMPs) in immune cells suggests that histones may be part of a larger antimicrobial mechanism in vivo. Here we report that histone H2A enters E. coli and S. aureus through membrane pores formed by the AMPs L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 75 publications
2
50
0
Order By: Relevance
“…(2020) ( Ballard et al., 2020 ) demonstrated that lysozyme and histones inhibited hyphal metabolic activity in A. fumigatus isolates in a dose-dependent manner, and imaging flow cytometry revealed that histones inhibited the germination of A. fumigatus conidia. Recently, it was demonstrated that histone H2A enters Escherichia coli and S. aureus through membrane pores formed by the AMPs LL-37 and magainin-2, depolarizing the bacterial membrane potential, and impairing membrane recovery ( Doolin et al., 2020 ). Once inside cell, H2A reorganizes bacterial chromosomal DNA, inhibiting global transcription, acting directly on killing of bacteria ( Doolin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) ( Ballard et al., 2020 ) demonstrated that lysozyme and histones inhibited hyphal metabolic activity in A. fumigatus isolates in a dose-dependent manner, and imaging flow cytometry revealed that histones inhibited the germination of A. fumigatus conidia. Recently, it was demonstrated that histone H2A enters Escherichia coli and S. aureus through membrane pores formed by the AMPs LL-37 and magainin-2, depolarizing the bacterial membrane potential, and impairing membrane recovery ( Doolin et al., 2020 ). Once inside cell, H2A reorganizes bacterial chromosomal DNA, inhibiting global transcription, acting directly on killing of bacteria ( Doolin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that histone H2A enters Escherichia coli and S. aureus through membrane pores formed by the AMPs LL-37 and magainin-2, depolarizing the bacterial membrane potential, and impairing membrane recovery ( Doolin et al., 2020 ). Once inside cell, H2A reorganizes bacterial chromosomal DNA, inhibiting global transcription, acting directly on killing of bacteria ( Doolin et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the two synergic partners shared a single target, but synergy may also arise from two different AMPs each one acting on their own and specific target in a concerted manner. The disruption of bacterial membranes by the human AMP LL-37 allows the histone H2A to gain access into the bacterial cytoplasm to interact with the bacterial genome, and to halt transcription [ 157 ]. Synergism is not limited to AMPs as exclusive partners; other actions or compounds may synergize with a given AMP to improve the final microbicidal aftermath.…”
Section: Synergy Of Cyanobacterial Peptidesmentioning
confidence: 99%
“…Although the cathelicidins exhibit antimicrobial activity against bacteria, viruses, fungi, and parasites, they also modulate inflammatory responses primarily via formyl peptide receptor 2/ALX (FPR2/ALX in humans or Fpr2/3 in mice) [ 7 , 8 , 9 ]. Notably, a recent study [ 10 ] has reported that histone H2A is able exert its antimicrobial activity in bacteria in conjunction with antimicrobial peptides, LL37 and magainin-2. H2A enters into bacteria such as Escherichia coli via the pores made by LL37 and/or magainin-2, and impairs the recovery of membrane and inhibits the bacterial transcription via reorganizing the chromosome.…”
Section: Introductionmentioning
confidence: 99%